2019
DOI: 10.22146/jcef.49395
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Radar Rainfall Estimates Based on Ground Elevation Function

Abstract: X-band radar gives several advantages for quantitative rainfall estimation, involving higher spatial and temporal resolution, also the ability to reduce attenuation effects and hardware calibration errors. However, the estimates error due to attenuation in heavy rainfall condition cannot be avoided. In the mountainous region, the impact of topography is considered to contribute to radar rainfall estimates error. To have more reliable estimated radar rainfall to be used in various applications, a rainfall estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The obs rain gauges are verified and calibrated regularly every year. Obs rain gauges validate remote sensing-based rainfall measurements such as radar and weather satellites [6]. Table 1 shows the location of the obs rain gauges and the coordinate grid based on the focus of the study area.…”
Section: Methodsmentioning
confidence: 99%
“…The obs rain gauges are verified and calibrated regularly every year. Obs rain gauges validate remote sensing-based rainfall measurements such as radar and weather satellites [6]. Table 1 shows the location of the obs rain gauges and the coordinate grid based on the focus of the study area.…”
Section: Methodsmentioning
confidence: 99%
“…[0, ∞) 0 (Hambali et al, 2019;Baig et al, 2022) Relative bias (RB) RB = Gupta et al, 1999;Farzana et al, 2019) where X observed rainfall; Y SPPs; and n amount of data. contributing factor to the use of SPPs in hydrological analyses.…”
Section: Data Descriptionmentioning
confidence: 99%
“…This radar rainfall station was still under study. Several studies have used radar rainfall data, such as in [2][3][4][5]. However, the researchers and the other users have not utilized the 3D features of the recorded radar rainfall data extensively.…”
Section: Introductionmentioning
confidence: 99%